The utilization of microalgae as an agent for converting CO2 to O2 in a photosynthesis reactor to mitigate CO2 emissions - Mahendra Satria Hadiningrat; Eggi Aunur Rofiq (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2021)
A closed photobioreactor design has been fabricated, aiming to determine the basic concept for microalgae Chlorella Vulgaris development. This study employed a flat-plate type with dimensions of 16x20x25 cm with the effectiveness of 3000 ml culture media and two 20 Watt 220 Volt Tungsten Halogen lamps, which were placed on the right and left sides of the reactor with a light intensity of 1000 lux. This study employed two photobioreactors, type I without CO2 supply and type II with CO2 supply as much as 25%. The initial cell density of Chlorella Vulgaris culture was 14,694 x105 cells/ml; then observations were made every day using a Haemocytometer. O2 concentration data were collected every day 3 times with irradiation time of 1, 6, and 9 hours using the O2 gas sensor (KE-50 type). The determination of the O2 concentration value in the photobioreactor on the 3rd day was 0.69%